Perbandingan Antara Pemberian Rebusan Daun Sirih Dan Daun Binahong Terhadap Keputihan Pada Wanita Usia Subur Di Wilayah Kelurahan Serua Ciputat Tangerang Selatan Tahun 2023 - Diana Awardi; Agnomelsya Bangaran; Nirmala Harahap (Indonesian Journal of Midwifery Scientific, 2024)
Leucorrhoea is a condition in which a woman experiences fluor albusthat is not normal. This can be experienced by all ages and is caused by various factors. There are two categories of vaginal discharge, namely physiological fluor albusand pathological vaginal discharge. To find out the comparison between betel leaf decoction and binahong leaves on fluor albusin women of childbearing age in the Serua Ciputat sub-district, South Tangerang, in 2023. This type of research is quasi-experimental research. The design uses two groups pre test and post test. The sampling technique used in this study used a purposive sampling technique. Based on the results of the Wilcoxon Test, there was a significant effect between the use of boiled betel leaves and binahong leaves on the incidence of fluor albusin women of childbearing age in the Serua Ciputat Village, South Tangerang where p<0.05. There is a relationship between giving boiled betel leaves and binahong leaves to fluor albus in women of childbearing age in the Serua Ciputat Subdistrict, South Tangerang in 2023. Respondents are expected to continue to increase knowledge about fluor albus and maintain the cleanliness of the genital organs to avoid unwanted fluor albus. normal. For future researchers, it is hoped that the results of this study can become a data base for conducting further research.